Polar mesosphere summer echoes during the July 2000 solar protonevent - V. Barabash; S. Kirkwood; A. Feofilov; A. Kutepov (Annales Geophysicae, 2004)
The influence of the solar proton event (SPE) 14–16 July 2000 on Polar Mesosphere Summer Echoes (PMSE) is examined. PMSE were observed by the Esrange VHF MST Radar (ESRAD) at 67°53'N, 21°06'E. The 30MHz Imaging Riometer for Ionospheric Studies IRIS in Kilpisjärvi (69°30'N, 20°47'E) registered cosmic radio noise absorption caused by ionisation changes in response to the energetic particle precipitation. An energy deposition/ion-chemical model was used to estimate the density of free electrons and ions in the upper atmosphere. Particle collision frequencies were calculated from the MSISE-90 model. Electric fields were calculated using conductivities from the model and measured magnetic disturbances. The electric field reached a maximum of 91mV/m during the most intensive period of the geomagnetic storm accompanying the SPE. The temperature increase due to Joule and particle heating was calculated, taking into account radiative cooling. The temperature increase at PMSE heights was found to be very small. The observed PMSE were rather intensive and extended over the 80–90km height interval. PMSE almost disappeared above 86km at the time of greatest Joule heating on 15 July 2000. Neither ionisation changes, nor Joule/particle heating can explain the PMSE reduction. Transport effects due to the strong electric field are a more likely explanation. Key words. Meteorology and atmospheric dynamics (middle atmospheric dynamics), ionosphere (ionospheric disturbances; solar radiation and cosmic ray effects)